Simulation of implant fitting in the femur bone / Nadia Mohd Ismail - Nadia , Mohd Ismail (2003)
In the past years, computer-assisted methods have become more and more accepted in the fields of orthopedic surgical treatments. This trend has been encouraged by the needs of more automated and digitized forms of aids to be used in the operation theater and also to assist pre-operation planning. Surgeons have long practiced using exhaustive methods and now seeking other tools to enhance their skills which will hopefully reduce traumas and produce better post-surgical outcomes. The emergence of high performance computing and graphics hardware changed the way medical data were analyzed. The development of virtual medical simulators has allowed healthcare providers to practice procedure without real dire consequence and establish skills, standards, and optimizations before actual surgery. An ideal medical simulation system will integrate the component of visualization, automated model generation, surgery simulation, and surgery assistance into one system. This thesis project aims to meet these criterion in developing a system specifically designed for implant fitting procedures in the human femoral anatomy. Three-dimensional model acquired from past researches will be manipulated using the software Geomagic Studio Version 5.0 and Rhinoceros 3.0 to build a customs-fitted implant model, which strives to be beneficial to the surgery procedures, as well as the parties involved; medical practitioners and patients alike.